A comparative study of the in vitro antitumor effect of mannose‐doxorubicin conjugates with different linkers. Issue 3 (3rd November 2021) - Cui, Xinxin; Du, Kunda; Yuan, Xiaoyin; Xiao, Wen; Tao, Yayu; Xu, Defeng; Hu, Hang
Abstract: In this work, five Man‐DOX conjugates with different linkers were developed for targeted DOX delivery. The five Man‐DOX conjugates with different linkers were characterized by 1 H NMR, HRMS, HPLC, UV–vis, and fluorescence spectroscopy. Man‐Suc‐DOX, Man‐TDG‐DOX, and Man‐DG‐DOX can self‐assemble into near‐spherical nanoparticles with hydrodynamic diameters of 150–200 nm and negative zeta potentials in deionized water, whereas Man‐SS‐DOX and Man‐SeSe‐DOX are hardly dispersed in deionized water. The self‐assembly behaviors of Man‐Suc‐DOX, Man‐TDG‐DOX, and Man‐DG‐DOX were studied by dissipative particle dynamics simulation and the results show that Man‐Suc‐DOX, Man‐TDG‐DOX, and Man‐DG‐DOX all self‐assemble into spherical particles with Man and linkers on the surfaces and DOX in the interiors. The in vitro drug release study shows that Man‐Suc‐DOX, Man‐TDG‐DOX, and Man‐DG‐DOX exhibit limited drug release, while Man‐SS‐DOX and Man‐SeSe‐DOX exhibit glutathione‐responsive drug release. The cellular uptake study shows that Man‐DG‐DOX exhibits the highest cellular uptake amount on HepG2 cells. Finally, Man‐DG‐DOX exhibits the best in vitro antitumor effect against HepG2 cells among the five Man‐DOX conjugates with different linkers. Although the in vitro antitumor activity of Man‐DG‐DOX is still lower than free DOX, Man‐DG‐DOX shows significant selectivity toward HepG2 cells. Man‐DG‐DOX might achieve selective DOX delivery for mannose receptor overexpressed tumors.